2016
DOI: 10.1016/j.quascirev.2016.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Drainage evolution of the Heihe River in western Hexi Corridor, China, derived from sedimentary and magnetostratigraphic results

Abstract: The uplifting of the Tibetan Plateau has significantly changed the environment in surrounding areas by delivering abundant water and sediment. The Heihe River draining the Qilian Shan in the NE Tibetan Plateau acts as a dominant sediment routing system from the uplifted NE Tibetan Plateau to the Hexi Corridor as well as the Badain Jaran Desert. Reconstructing the evolution of the Heihe River could provide evidence for the birth of the Badain Jaran Desert and enhance the understanding of sedimentary basin fill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
(99 reference statements)
1
19
0
Order By: Relevance
“…In this sense the first order chronology of the GN200 is confirmed by findings of Pan et al (2016) and their cores from the Heihe fluvial/alluvial plains in the Hexi Corridor. Thus, the mega-sequence forming unit C in GN200 is a coarsening up succession that represents the arrival and progradation of the Heihe alluvial fan in the Ejina Basin.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this sense the first order chronology of the GN200 is confirmed by findings of Pan et al (2016) and their cores from the Heihe fluvial/alluvial plains in the Hexi Corridor. Thus, the mega-sequence forming unit C in GN200 is a coarsening up succession that represents the arrival and progradation of the Heihe alluvial fan in the Ejina Basin.…”
Section: Discussionsupporting
confidence: 63%
“…An upcore enhanced chlorite load, which to some extent is paralleled by an enhanced dolomite load in units B and C, may support this interpretation; chlorite 465 is known to be exposed in basaltic bedrock outcropping in the Qilian Shan and so is dolomite; both minerals are interpreted to be indicative provenance minerals of the southern catchment (Song et al, 2009;Schimpf, 2019), which increase in the Ejina Basin with the arrival of Heihe river sediments. Pan et al (2016) discussed a previous study, which suggested that the Shiyang River (400 km SE from Heihe) formed approximately 1.2 Ma (Pan et al, 2007), based on studies of the highest fluvial terraces. This age is consistent with the 470 formation age of the Tengger Desert (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Previous work suggested that alluvial/fluvial fan areas of the Heihe River and Shiyanghe River are the dominant source for sandy material in the Badain Jaran and Tengger Deserts (Yang et al, 2012;Wang et al, 2015;Hu and Yang, 2016). Thus, the formation of both deserts was to a large extent determined by the evolution of the Heihe River and Shiyanghe River, the formation ages of which were both dated to 1.2-0.9 Ma (Pan et al, 2003(Pan et al, , 2007(Pan et al, , 2016. In the case of the Hobq Desert, the aeolian sand mainly originated from the reworking of the fluvial-lacustrine sediments in the Hetao Basin.…”
Section: Formation Of the Hobq Desertmentioning
confidence: 97%
“…The lack of long and continuous sedimentary records from the area has impeded paleoclimatic research of the transitional zone of the EASM and the westerlies. A sedimentary record from the Jiudong subbasin since ~1.8 Ma was presented previously (Pan et al, 2016), and the sediments clearly offer the opportunity to reconstruct the long-term climatic evolution of the area.
Figure 1.(color online) Location of the NE Tibetan Plateau and the study area.
…”
Section: Introductionmentioning
confidence: 92%
“…1). The annual rainfall is 80–130 mm (Pan et al, 2016), with 60% concentrated in June, July, and August. The annual pan evaporation is more than 1900 mm (Chen and Qu, 1992), and the annual temperature is approximately 7°C–8°C (Pan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%